Angiotensin-Converting Enzyme Receptor Genotype and its Activity Level as Potential Predictors of the Severity COVID-19 among Iraqi Patients - Kamel, Suzan Haleem; Al-Tu'ma, Fadhil Jawad; Al-Saegh, Riyadh Mohi (Journal of Contemporary Medical Sciences, 2021)
Objectives: The purpose of this study is to determine whether the angiotensin-converting enzyme activity and various biomarkers are used to investigate the severity of Covid-19 and to study the genetic variation occurs in angiotensin-converting enzyme-2 (ACE-2) receptor in severe Covid-19-related genes in the Iraqi population of Kerbala Province. Methods: This case-control study was conducted on 176 subjects who survived hospitalization and diagnosed by physician. Various biomarkers including ferritin, C-reactive protein, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase, angiotensin-converting enzyme-2 activity levels were determined. Accordingly, they were divided into three groups: 59 of them were infected with severe Covid-19, 54 of them were infected with moderate Covid-19 and 63 of them were checked and obtained as apparently healthy control. Severe and moderate patients were collected from Al-Hayat tertiary center at Al-Hussein Medical City, Kerbala Health Directorates, Kerbala – Iraq during Oct., 2020- July, 2021 with matched age ranged between (23-88) years. Blood samples of apparently healthy and Covid-19 samples were subjected to genomic DNA extraction within 24-48 hours of aspiration. The genomic DNA extracted was subjected to electrophoresis through 1.5% of agarose gels which was detected by staining with the fluorescent dye ethidium bromide and then visualized by illumination with UV light to confirm the presence and integrity of the extracted DNA. Results: Genotyping of ACE-2 (I/D) polymorphism (rs4646994), which has a high prevalence, was performed by polymerase chain reaction assay. The amplification of an Alu repetitive element in an intron of the ACE-2 has shown three potential genotypes of I/I and D/D as homozygous, and I/D as heterozygous. Individuals with normal homozygous (DD) revealed band of (190 bp), while individuals with normal (II) revealed band of (490 bp), and the individuals with heterozygous (ID) revealed two bands (190, 490 bp) respectively. Every severe Covid-19 group carried (DD) allele genotype, moderate group carried (ID and II) alleles and finally the control group carried (DD, ID, II) alleles genotype. Conclusion: In the ACE-2 polymorphism, the D/D genotype allele is implicated as a risk factor for severe Covid-19 patients, in Iraqi population.